(3GUhd GdGKHGJ aj GdehGO GdeOfjI h GdJLGQjI (B/s - (3RgQGf, geGe eMeO eMehOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3eMd GdEKHGJ , GdCUd aj JMOjO Gdecda HYHF GdEKHGJ, SHd JMUjd GdMbjbI GdbVGFjI ,COdI GdEKHGJ GdCOdI GdeWdbI ,GdCOdI GdebjOIs
Keywords: (3GdEKHGJs; (3GdbGfhfs